Do the Characteristics of Startup Founders Matter for Funding Performance? - Brahmana, Rayenda Khresna; Setiawan, Doddy; Lau, Evan; Kontesa, Maria (Journal of Indonesian Economy and Business, 2024)
Introduction/Main Objectives: Based on the upper echelons theory, this research examines the role of startup founders' characteristics on startup funding performance (SFP). This study considers the founder's experience, education, and gender as the characteristics that positively affect the SFP. Background Problems: While academia and industry emphasize the importance of startup funding performance (SFP), the empirical evidence on its determinant has received less attention. Yet, upper echelons theory addresses the importance of a leader's characteristics in increasing the organization's performance. Therefore, the current study focuses on investigating the role of startup founders' characteristics in the SFP. Novelty: The current study proposes the founder's characteristics as the key factor for startup funding. Unlike previous studies, this study utilized a survey design to answer the research question. Additionally, this study is the pioneer for entrepreneurial finance studies in gauging the upper-echelons framework. Research Methods: This research collected information from 228 Indonesian Startups through a survey. The estimation model is estimated using robust cross-sectional OLS regression and logistic regression. For robustness purposes, this study tackles the endogeneity issue by using two-stage least squares (TSLS) and PLS-SEM. Finding/Results: The regression results (including the two-stage least square approach) reveal that education and gender play a significant role in SFP but not experience. Moreover, it shows that higher education would increase a startup's probability of having better funding. Meanwhile, male entrepreneurs have lower funding performance than women entrepreneurs. Conclusion: Our study surmises that the education of the founders is crucial for startup financing in Indonesia. It also shows that the experience of founders has a trivial effect. It supports the upper echelons theory, emphasizing the pivotal role of founders' characteristics in entrepreneurial finance. Policy-wise, focusing on education can enhance startup success while addressing gender disparities is crucial. However, limitations exist, suggesting the need for longitudinal studies and broader sample sizes. Future research could explore managerial abilities and cultural factors, offering fresh insights into the literature.